An Energy and Load Aware Multipath Routing Protocol in Internet of Things - Khaleghnasab, Roghaye; Bagherifard, Karamolah; Parvin, Hamid; Nejatian, Samad; Ravaei, Bahman (Management Strategies and Engineering Sciences, 2025)
IoT is a network of smart things. This indicates the ability of these physical things to transfer information with other physical things. The characteristics of these networks, such as topology dynamicity and energy constraint, challenges the routing problem in these networks. Previous routing methods could not achieve the required performance in this type of network. One of the routing methods is utilization of multipath protocols which send data to its destination using routes with separate links. One of such protocols is RPL routing protocol. In this paper, this method is improved using composite metrics which chooses the best paths used for separate routes to send packets. the protocol of Energy and Load aware RPL (ELaM-IoT), has been suggested that it has a rise of RPL protocol. It applies a composite metric, estimated based upon the extant energy, hop count, load & battery depletion index, and Link Expiration Time, for the selection of route. In order to evaluate and report the results, the proposed ELaM-IoT method is compared to the ERGID and ADRM-IoT approaches with regard to average remaining energy, and network lifetime. The results demonstrate the superior performance of the proposed ELaM-IoT compared to the ERGID and ADRM-IoT approaches.